Communication, International Media, and the Creation of Soft Power of Countries: An atypical review and discussion - Dr. Safran Safar Almakaty (Journal of Advanced Research in Journalism & Mass Communication, 2024)
This research paper explores the pivotal role of communication and international media in the development of national soft power, a concept popularized by Joseph Nye. It examines how countries can effectively utilize media to influence international relations and cultural diplomacy, thereby enhancing their global standing without recourse to force. The investigation includes an extensive review of literature that connects the rise of digital media platforms with increasing opportunities for nations to project soft power more dynamically and extensively than ever before. Methodologically, the paper employs a qualitative approach, analyzing a variety of case studies that illuminate the strategies different countries employ. These case studies not only exemplify effective media utilization in varied global contexts but also reveal the adaptability required to tailor media strategies to specific cultural and political landscapes. The findings from this study emphasize the transformative power of both traditional and digital media in shaping international perceptions and advancing diplomatic goals. The results suggest that a well-articulated media strategy can significantly augment a nation's ability to attract and persuade, thereby increasing its soft power. The paper concludes by proposing several directions for future research, focusing particularly on how emerging technologies might further influence the efficacy of soft power initiatives. Additionally, it offers strategic recommendations for policymakers and media experts aiming to craft more effective global communication and diplomacy strategies. This research contributes to a deeper understanding of the strategic use of media in international relations, providing insights that are crucial for anyone involved in diplomacy, media strategy, and global policy formulation.